Networking in late medieval Central Europe : friends, families, foes - Możejko, Beata; Orłowska, Anna Paulina; Carr-Riegel, Leslie (2023)
"Exploring the formation of networks across late medieval Central Europe, this book examines the complex interaction of merchants, students, artists and diplomats in a web of connections that linked the region. These individuals were friends in business ventures, occasionally families, and not infrequently foes. No single activity linked them, but rather their interconnectivity through matrices based in diverse modalities was key. Partnerships were not always friendship networks, art was sometimes passed between enemies, and families created for financial gain. Taking an interdisciplinary approach, the chapters focus on inclusion and exclusion within intercultural networks, both interpersonal and artistic, using a wide spectrum of source materials and methodological approaches. The concept of friends is considered broadly, as connections of mutual affection but also simply through business relationships. Families are considered in terms of how they helped or hindered local integration for foreigners and the matrimonial strategies they pursued. Networks were also deeply impacted by rivalry and hostility